The importance of in-service training in restructuring sectors - ORAL, BÜLENT; SAĞLAM, ŞAFAK (ELSEVIER SCIENCE BV, 2010)
Reduction or abolishment operation of government's intervention to economy, accelerating since the beginning of 1980s, is adopted by many governments as governance policy. This policy, being widely used in manufacturing industry and service sector at the beginning, has been used subsequently in electricity, natural gas, water ... etc industry as natural monopoly. The employee needs to know position at institution organization, individual value and expectations. It is effective on the employee performance. In this context, the employees can take in-service education their institutions and regulatory authorities, which regulate and supervise the sectors. The in-service education plan is supported the program content and process by academic circles. In this study, it is emphasized process and content of scheduled in-service education program.
Keywords: In-service education; in-service training; deregulation; restructuring; market economy; PRIVATIZATION